2020
DOI: 10.1016/j.stem.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered Spatial Transcriptomics Identify Secretory Factors Promoting Human Hematopoietic Stem Cell Development

Abstract: Summary Hematopoietic stem cells (HSCs) first emerge in the embryonic aorta-gonad-mesonephros (AGM) region. Studies of model organisms defined intersecting signaling pathways that converge to promote HSC emergence predominantly in the ventral domain of the dorsal aorta. Much less is known about mechanisms driving HSC development in humans. Here, to identify secreted signals underlying human HSC development, we combined spatial transcriptomics analysis of dorsoventral polarized signaling in the aorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 129 publications
8
69
0
Order By: Relevance
“…We noted that a proportion of Aplnr -tdTomato-positive cells also expressed hematopoietic markers implying that it is expressed at the EHT transition stage. This is in keeping with single-cell sequencing analyses of human AGM implying that APLNR was expressed in hemogenic endothelium ( Crosse et al., 2020 ). Two further studies have reported the downregulation of Aplnr as endothelial cells acquire hematopoietic markers during EHT ( Bruveris et al., 2020 ; Oatley et al., 2020 ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We noted that a proportion of Aplnr -tdTomato-positive cells also expressed hematopoietic markers implying that it is expressed at the EHT transition stage. This is in keeping with single-cell sequencing analyses of human AGM implying that APLNR was expressed in hemogenic endothelium ( Crosse et al., 2020 ). Two further studies have reported the downregulation of Aplnr as endothelial cells acquire hematopoietic markers during EHT ( Bruveris et al., 2020 ; Oatley et al., 2020 ).…”
Section: Discussionsupporting
confidence: 84%
“…The Apelin receptor gene ( Aplnr/Agtrl1/Apj ) encodes a member of the G protein-coupled receptor family and has been implicated in cardiac, endothelial, and hematopoietic development in a number of model systems ( D'Aniello et al., 2009 ; Inui et al., 2006 ; Quertermous, 2007 ; Scott et al., 2007 ). Pertinent to this study is the involvement of Aplnr Aplnr in endothelial cell maturation during development and the fact that it appears to be expressed at a higher level in endothelial cells of the AGM region, implying that it could be related to their hemogenic potential both in mouse ( Kidoya et al., 2015 ; Kidoya et al., 2008 , 2010 ) and human embryos ( Crosse et al., 2020 ). In the adult bone marrow, endothelial cells that express APELIN, one of the APLNR ligands, participate in vascular remodeling after irradiation and drive post-transplant recovery through feedback from HSPCs ( Chen et al., 2019 ).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations